Choice of Locations by Foreign Investors: Motives for and Factors of Starting a Manufacturing Activity (the Example of Selected Factories in Poland) - Tobolska, Anna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
The choice of a location is one of the most important decisions taken by an enterprise, both at start-up and at other stages of its life cycle involving a relocation of activity or a spatial fragmentation of the chain of value-added generation. The choice of a location by an enterprise is also of great significance for the development of the region selected, its economic and social structure, and the pattern of its spatial links. That is what makes the choice of a location one of major research problems in socio-economic geography, and in particular in its sub-discipline - industrial geography, with its scope of research embracing issues in location theory and factors of the location of enterprises and industrial plants.This paper offers an analysis of the location factors of selected factories - affiliates of international corporations, in terms of their strategic decisions of expansion onto markets abroad in the form of foreign direct investment (FDI). For international corporations, the choice of a new place of economic activity is closely connected with global advantages of conducting business at the international scale and with motives for their internationalisation.